(untitled) (Revista Torreón Universitario, 2015)
The quality of being in the interior regions of our countries and their regional structures that each of our nations have, especially, because this is an issue that not only has a historical basis, but it is also a theme of extraordinary relevance for the meaning on which we are part of globalization. That so far has a predominantly neoliberal trend, but an increasing number of countries that are engaged in profound changes in transformation processes are trying to change to be part of the future and not just recipients of what he has taught us as transnational capital.